Dynamic Interaction of Train-Bridge Systems in High-Speed Railways Theory and Applications - Xia, He.; Zhang, Nan.; Guo, Weiwei; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2018)
This book presents both the fundamental theory and numerical calculations and field experiments used in a range of practical engineering projects. It not only provides theoretical formulations and various solutions, but also offers concrete methods to extend the life of existing bridge structures and presents a guide to the rational design of new bridges, such as high-speed railway bridges and long-span bridges. Further, it offers a reference resource for solving vehicle-structure dynamic interaction problems in the research on and design of all types of highways, railways and other transport structures.
Introduction to coupling dynamics of train-bridge system -- Fundamentals of bridge response under moving loads -- Design codes for high-sped railway bridges in China -- Dynamic modeling of coupling train-bridge system -- Dynamic analysis of train-bridge system subjected to wind action -- Dynamic analysis of train-bridge system subjected to seismic action -- Dynamic analysis of train-bridge system subjected to collision loads -- Damage identification of bridge structure based on train/bridge responses.
Keywords: Multibody systems; Vibration; Mechanics, Applied; Light construction; Steel construction; Lightweight construction; Transportation engineering; Traffic engineering; Multibody Systems and Mechanical Vibrations; Light-weight Construction, Steel and Timber Construction; Transportation Technology and Traffic Engineering